HERMENEUTIKA DALAM KAJIAN ALQURAN DAN URGENSINYA DALAM PENDIDIKAN ISLAM - Ali, Mohammad (Institut Agama Islam Negeri (IAIN) Palu, 2008)
This paper deals with the hermeneutical approach to the Quran and its relation to Islamic education. It is argued that hermeneutic assumes the relativity of any interpretation since it has been influenced by different context and environmentsâ be they social, cultural, or politicalâthat surround the interpreter. Therefore, Islamic education, which associated with the interpretation of the Quran and the Prophetic traditions as primary sources, should be reinterpreted according to modern demands based on moral values or ideal morals which become the spirit of revelation of the text.Kata Kunci: hermeneutika, kajian Alquran, pendidikan Islam Â Â